ПОРАДА ЯК СУГЕСТИВНИЙ СКЛАДНИК УКРАЇНСЬКОГО МЕТЕОДИСКУРСУ (World Science, 2020)
The aim of this study is to elucidate the pragmatic and language specificity of advice as a suggestive component of Ukrainian meteorological discourse. The weather forecasts published on air of the radio station Kraina FM by Natalka Didenko were the observation material. The subject of the study is the communicative-pragmatic parameters of autumn and winter advice of the weather forecaster. Advice in meteorological discourse is implemented in several pragmatic variants: recommendation, warning, prohibition, proposal and appeal. Every type is aimed at preserving life and health of the population, rational organization of work, everyday routine and rest, consolidation of the population with regard to national and universal human values. Within the limits of advice professional and “non-professional” advice are distinguished, which implemented professional and “nonprofessional” intentions of the weather forecaster. Serious and humorous advice of a proactive nature has been noticed. Means of expression are imperatives, indicatives, modal and negative constructions. There is an integration of publicistic, scientific, colloquial and belles-letters styles in the meteorological advice that provide its necessary suggestiveness.